Association of Cervical Spondylosis with Recurrence of Benign Paroxysmal Positional Vertigo: a case report - Nimra, Binash Afzal, Ayesha Zulfiqar, Taiba Azam, Sadaf Ghulam, (Pakistan Journal of Medical & Health Sciences, 2022)
Benign Paroxysmal Positional Vertigo is thought to be the main cause of vertigo globally. It is recurrent and remediable disease accounts under peripheral vestibular disorder which involve one or more then on semicircular canal with floating and displaced otoconia. Activated afferents of semicircular canals produce false sensation of nystagmus. It is characterized by scanty spinning sensations initiated by head movements, commonly in the vertical or horizontal planes. BPPV is common in elderly population and is often undiagnosed or misdiagnosed. BPPV is mostly diagnosed by history and complete examination which involve the Dix-Hallpike maneuver consider as gold standard maneuver in assessment. BPPV is mostly treated conservatively utilizing various physiotherapeutic techniques. Patient education, Semont maneuver (SM), Epley maneuver, Brandt Daroff along with vestibular rehabilitation exercises are proven to be effective in improving sensations of vertigo and chances of reoccurrence. Keywords: Benign Paroxysmal Positional Vertigo, Cervical Spondylosis, Association